ISSUES OF THE EDUCATOR’S SPEECH CULTURE IN THE TEACHING AND EDUCATIONAL PROCESS - O’rinboyeva Laylo; Kalandarova Fazilat (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
The speech culture of educators in the teaching and upbringing process is one of the important directions of modern pedagogical science. This article deeply analyzes the influence of the educator’s speech culture on the effectiveness of the educational process, as well as its psychological, linguistic, and ethical aspects. Speech culture is emphasized not only as a means of transmitting information but also as a decisive factor in personal development, social relations, and the formation of national values. The article covers the structural components of speech culture, factors hindering its development, and scientific-methodological approaches to its improvement. The research results are enriched with practical recommendations for enhancing the speech competence of educators in educational institutions. The conducted analyses demonstrate the necessity of considering speech culture as a strategic resource in the modern education system.